Impact of g force and timing on the characteristics of platelet-rich fibrin matrices - Ana B. Castro (Nature Portfolio, 2021)
Abstract Recently, new centrifugation protocols for the preparation of platelet-rich fibrin (PRF) have been introduced in an attempt to further improve the beneficial impact of these 2nd generation platelet concentrate membranes. This in-vitro study aimed to compare the biological and physical characteristics of three types of PRF membranes using two different centrifuges with adapted relative centrifugal forces (RCF): leucocyte- and platelet-rich fibrin, advanced platelet-rich fibrin, and advanced platelet-rich fibrin+. Release of growth factors, macroscopic dimensions, cellular content and mechanical properties of the respective membranes, prepared from blood of the same individual were explored. Furthermore, the impact of timing (blood draw-centrifugation and centrifugation-membrane preparation) was assessed morphologically as well as by electron microscopy scanning. No statistically significant differences amongst the three PRF modifications could be observed, neither in their release of growth factors or the cellular content, nor in clot/membrane dimensions. The difference between both centrifuges were negligible when the same g-force was used. A lower g-force, however, reduced membrane tensile strength. Timing in the preparation process had a significant impact. Adaptation of RCF only had a minimal impact on the final characteristics of PRF membranes.